Too much of a good thing: a case report of traumatic drop attacks and syncope due to orthostatic hypertension. Issue 1 (12th December 2020) - von Bartheld, Martin B; Duffels, Mariëlle G J; Handoko, M Louis
Abstract: Background: Orthostatic hypertension (OHT) is the clinical opposite to orthostatic hypotension and is an under-recognized and poorly understood clinical phenomenon. Patients may experience disabling symptoms such as dizziness, chest pain, and shortness of breath. In addition, OHT is associated with important clinical outcomes such as silent cerebral infarcts and cognitive decline. Case summary: We present the case of a 67-year-old female who experienced frequent drop attacks with and without transient loss of consciousness causing various injuries. A range of standard diagnostic procedures did not yield an explanation for her symptoms but head-up tilt (HUT) testing showed OHT and induced most of her symptoms. Upon initiation of doxazosin, an alpha-blocking drug, she was free of symptoms and blood pressure response was normal on the repeat HUT test. Discussion: To our knowledge, this is the first report of syncope due to OHT. Orthostatic hypertension is a heterogeneous condition and may occur in young, otherwise healthy individuals but also in older patients with cardiovascular comorbidities. It is thought that symptoms occur because of excessive venous pooling (causing a drop in cardiac output) or adrenergic hypersensitivity (resulting in cerebral vasoconstriction or acute rise in cardiac afterload). Since our patient had a marked response to an alpha-blocking agent, we think baroreflex hypersensitivity is the most likely cause of her complaints. Though syncope is probably rare, OHT should be regarded as a possible explanation of orthostatic symptoms.